Сочинение в начальной школе по картинкам (2013)
Ил. на одной стороне л. - Режим доступа: http://elibrary.unatlib.org.ru/handle/123456789/8693 Экземпляры: НЭБ (20140227) / Инвентарный номер: PDF000179 / Сис.шифр: 74.26 / Авт.знак: М 69 / ГРНТИ: 14 / ББК: 74.268.19=411.2,0